Influence of flood risk perception and other factors on risk‐reducing behaviour: a survey of municipalities along the Rhine. Issue 1 (7th February 2013) - Becker, G.; Aerts, J.C.J.H.; Huitema, D.
Abstract A survey of German public officials responsible for municipal flood management along the Rhine has been carried out to assess their perceptions of flood risk and protective behaviour. A sociopsychological framework based on expectancy‐valence models was used to develop an overview of potentially important factors in prompting action to avoid flood damage. The applied framework was confirmed as a useful tool to get more insight into the risk‐reducing processes in the public‐sector sphere. The study delivers valuable guidance on those factors, which should be given more attention in order to improve the level of preparedness and to reduce flood losses.